Novel Mutations Within Collagen Alpha1(I) and Alpha2(I) Ligand-Binding Sites, Broadening the Spectrum of Osteogenesis Imperfecta – Current Insights Into Collagen Type I Lethal Regions - Sałacińska, Kinga; Pinkier, Iwona; Rutkowska, Lena; Chlebna-Sokół, Danuta; Jakubowska-Pietkiewicz, Elżbieta; Michałus, Izabela; Kępczyński, Łukasz; Salachna, Dominik; Jamsheer, Aleksander; Bukowska-Olech, Ewelina; Jaszczuk, Ilona; Jakubowski, Lucjusz; et al. (Frontiers in Genetics, 2021)
Osteogenesis imperfecta (OI) is a rare genetic disorder demonstrating considerable phenotypic and genetic heterogeneity. The extensively studied genotype-phenotype correlation is a crucial issue for a reliable counselling, as the disease is recognized at increasingly earlier stages of life, including prenatal period. Based on population studies, clusters in COL1A1 and COL1A2 genes associated with the presence of glycine substitutions leading to fatal outcome have been distinguished and named as “lethal regions”. Their localization corresponds to the ligand-binding sites responsible for extracellular interactions of collagen molecules, which could explain high lethality associated with mutations mapping to these regions. Although a number of non-lethal cases have been identified from the variants located in lethal regions, the mortality rate of mutations has not been updated. An NGS analysis, using a custom gene panel of known and candidate OI genes, was performed on a group of 166 OI patients and revealed seven individuals with a causative mutations located in the lethal regions. Patients age, ranging between three to 25 years, excluded the expected fatal outcome. The identification of non-lethal cases caused by mutations located in lethal regions prompted us to determine the actual mortality caused by glycine substitutions mapping to lethal regions and evaluate the distribution of all lethal glycine mutations across collagen type I genes, based on records deposited in the Osteogenesis Imperfecta Variant Database. Finally, we identified six glycine substitutions located in lethal regions of COL1A1 and COL1A2 genes, of which four are novel. The review of all mutations in the dedicated OI database, revealed 33 distinct glycine substitutions in two lethal domains of COL1A1, 26 of which have been associated with a fatal outcome. Similarly, 109 glycine substitutions have been identified in eight lethal domains of COL1A2, of which 51 have been associated with a fatal manifestation. An analysis of all glycine substitutions leading to lethal phenotype, showed that their distribution along collagen type I genes is not regular, with 17% (26 out of 154) of mutations reported in COL1A1 and 64% (51 out of 80) in COL1A2 corresponding to localization of the lethal regions.